Structural color in Junonia butterflies evolves by tuning scale lamina thickness - Thayer, Rachel C; Allen, Frances I; Patel, Nipam H (eLife, 2020)
In diverse organisms, nanostructures that coherently scatter light create structural color, but how such structures are built remains mysterious. We investigate the evolution and genetic regulation of butterfly scale laminae, which are simple photonic nanostructures. In a lineage of buckeye butterflies artificially selected for blue wing color, we found that thickened laminae caused a color shift from brown to blue. Deletion of the optix patterning gene also altered color via lamina thickening, revealing shared regulation of pigments and lamina thickness. Finally, we show how lamina thickness variation contributes to the color diversity that distinguishes sexes and species throughout the genus Junonia. Thus, quantitatively tuning one dimension of scale architecture facilitates both the microevolution and macroevolution of a broad spectrum of hues. Because the lamina is an intrinsic component of typical butterfly scales, our findings suggest that tuning lamina thickness is an available mechanism to create structural color across the Lepidoptera.
Keywords: thin film; artificial selection; iridescence; wing pattern; optix